The Effect of Financial Performance on Stock Performance in the Banking Industry Listed on the Indonesia Stock Exchange - Muhammad Fauzy Ismail; Susy Muchtar (Majapahit Journal of Islamic Finance and Management, 2026)
This research aims to gain insight into the influence of a bank's financial performance on its market performance assuming that the financial performance of an organization is the most important criterion that triggers stock price movements. The data used in this study is secondary data sourced from the annual banking report listed on the Indonesia Stock Exchange (IDX) from 2020 – 2024. The number of research samples was 29 banks with a total of 145 data that met the criteria. This study used multiple linear regression analysis on panel data to evaluate the relationship between independent and dependent variables using e-views software 9. The results of this study show that net non-performing assets and current account savings accounts have a significant negative impact on share price growth. Capital adequacy ratio, net interest margin, and liquid assets total assets have a significant positive impact. Bank size has a significant positive impact. The implications of this research can be useful for managers to evaluate financial performance and strategies that affect market perception and also investors to consider external factors such as economic conditions and market sentiment.